2015
DOI: 10.1111/jsbm.12187
|View full text |Cite
|
Sign up to set email alerts
|

The Interdependence of R&D Activity and Debt Financing of Young Firms

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung der KfW und des ZEW dar.Dis cus si on Papers are inten ded to make results research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces sa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 69 publications
0
3
1
Order By: Relevance
“…Therefore, statistically, DER does not have a significant effect on TATO. This study was not in line with the findings of (Fryges et al, 2015), and (Mahendra, 2015) which stated that the use of funding sources from debts can improve firm activities through the improvement of R&D and firm innovation.…”
Section: Conclusion and Recommendationcontrasting
confidence: 91%
See 1 more Smart Citation
“…Therefore, statistically, DER does not have a significant effect on TATO. This study was not in line with the findings of (Fryges et al, 2015), and (Mahendra, 2015) which stated that the use of funding sources from debts can improve firm activities through the improvement of R&D and firm innovation.…”
Section: Conclusion and Recommendationcontrasting
confidence: 91%
“…In the signalling theory, it is explained that a company that has courage in using debts as its capital source means that it can optimally use the funding, consequently, the gained earnings will be able to cover the expenses of the use of the debts. The use of funding sources from debts can improve R&D activities (Fryges et al, 2015). The use of debts disciplines the company management and directs it to behave in line with the purpose of the company.…”
Section: The Effect Of Capital Structure On Total Asset Turnovermentioning
confidence: 99%
“…Contrasting results about the relative importance of debt are obtained in Fryges, Kohn, and Ullrich (2015) and Brown et al (2012). Whereas Fryges, Kohn, and Ullrich (2015), analysing 2007 German data, find a positive and perhaps two-way relationship between bank debt and R&D intensity, Brown et al (2012) found a negative relationship between hightech firms and the use of bank loans for the period 2007-2009.…”
Section: Innovation and Firm Capital Structurementioning
confidence: 94%
“…Extant empirical research shows that start-ups are often forced to raise external funds because they lack internal finance (Fryges, Kohn, and Ullrich 2015). Moreover, new firms have to deal with credit rationing due to their higher asymmetric information levels than larger and older firms (Carpenter and Petersen 2002b;Stiglitz and Weiss 1981).…”
Section: Information Asymmetries and Capital Structure Of New Firmsmentioning
confidence: 99%